Naukowe a zdroworozsądkowe rozumowanie praktyczne w nauczaniu = Scientific versus common sense practical reasoning in teaching of literature - Biłos, Edward (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Justifying the thesis that the present level of development of teaching of literature at school and the corresponding meditationis, descriptively-explanatory or methodological in character, as well as practical solutions of methodic problems can hardly he described as scholarly, the author discusses specific character of scholarly and common sense ways of reasoning in the process of instruction.
Keywords: nauczanie